Pharmacokinetics of the novel oral prostacyclin receptor agonist selexipag in subjects with hepatic or renal impairment - Kaufmann, Priska; Cruz, Hans G; Krause, Andreas; Ulč, Ivan; Halabi, Atef; Dingemanse, Jasper (British journal of clinical pharmacology, 2016)
AIM: The aim of the present study was to explore the effect of hepatic or renal dysfunction on the pharmacokinetics (PK), tolerability and safety of selexipag, an orally active prostacyclin receptor agonist. METHODS: Two prospective, open-label studies evaluated the PK of selexipag and its active metabolite ACT-333679 in healthy subjects and in subjects with mild, moderate and severe hepatic impairment or severe renal function impairment (SRFI). A single dose of 200 μg or 400 μg was administered. The PK parameters were derived from plasma concentration-time profiles. RESULTS: Exposure increased with the severity of hepatic impairment. Geometric mean ratios and 90% confidence intervals of the area under the concentration-time curve from time zero to infinity (AUC0-∞ ) for selexipag and ACT-333679 increased 2.1-fold (1.7-2.6) and 1.2-fold (0.9-1.6) in subjects with mild hepatic impairment, and 4.5-fold (3.4-5.8) and 2.2-fold (1.7-2.8) in subjects with moderate hepatic impairment when compared with healthy subjects. The two subjects with severe hepatic impairment showed similar dose-normalized exposure to that of subjects with moderate hepatic impairment. A 1.7-fold increase in the AUC0-∞ of selexipag and ACT-333679 was observed with SRFI compared with healthy subjects. Although exposure to selexipag and/or ACT-333679 was higher in subjects with mild or moderate hepatic impairment or SRFI vs. healthy subjects, no safety concerns were raised in these groups. CONCLUSIONS: Based on these observations, the PK data suggest that the clinically used starting dose needs no adjustments in patients with mild or moderate hepatic impairment or SRFI. However, doses should be up-titrated with caution in these patients. The small number of subjects limits the interpretation of selexipag PK in subjects with severe hepatic impairment.
Keywords: Acetamides; Pyrazines; Humans; Case-Control Studies; lidé středního věku; nemoci ledvin; studie případů a kontrol; receptory epoprostenolu; Liver Diseases; Dose-Response Relationship, Drug; Female; Aged; Area Under Curve; dospělí; Antihypertensive Agents; senioři; lidé; acetáty; Adult; acetamidy; nemoci jater; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; pyraziny; Receptors, Epoprostenol; Severity of Illness Index; plocha pod křivkou; vztah mezi dávkou a účinkem léčiva; Acetates; antihypertenziva; mužské pohlaví; prospektivní studie; Kidney Diseases; Prospective Studies